2009
DOI: 10.1002/elps.200800619
|View full text |Cite
|
Sign up to set email alerts
|

Studies of electroosmotic flow and the effects of protein adsorption in plasma‐polymerized microchannel surfaces

Abstract: This paper presents a study of EOF properties of plasma-polymerized microchannel surfaces and the effects of protein (fibrinogen and lysozyme) adsorption on the EOF behavior of the surface-modified microchannels. Three plasma polymer surfaces, i.e. tetraglyme, acrylic acid and allylamine, are tested. Results indicate EOF suppression in all plasma-coated channels compared with the uncoated glass microchannel surfaces. The EOF behaviors of the modified microchannels after exposure to protein solutions are also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 58 publications
0
42
0
Order By: Relevance
“…Figure 3 shows that uncoated PDMS avidly adsorbed fibrinogen, a material property characterized in previous studies. 22,42,44,57 The ppTTg coated silicon wafer again showed significant reductions in protein adsorption compared to uncoated PDMS, although not complete protein resistance. Double ppTTg clearly demonstrated very similar properties to those achieved on the positive control samples.…”
Section: Functionality Of Ppttg Coatingsmentioning
confidence: 94%
See 2 more Smart Citations
“…Figure 3 shows that uncoated PDMS avidly adsorbed fibrinogen, a material property characterized in previous studies. 22,42,44,57 The ppTTg coated silicon wafer again showed significant reductions in protein adsorption compared to uncoated PDMS, although not complete protein resistance. Double ppTTg clearly demonstrated very similar properties to those achieved on the positive control samples.…”
Section: Functionality Of Ppttg Coatingsmentioning
confidence: 94%
“…40 Lopez et al first showed that it was possible to produce protein resistant, ether carbon-rich films from glyme molecules using plasma polymerization. 41 The application of glyme, and a range of other plasma polymer inside glass and Teflon microfluidic devices, have been demonstrated to produce coatings with a range of specific surface charges, 42 spontaneous protein immobilization properties 43 and resistance to protein adsorption. 44 While a limited number of groups have access to dedicated plasma polymerization systems, it is possible that existing O 2 plasma units could be adapted for monomer handling or small chambers built from these systems at minimal cost.…”
Section: B)mentioning
confidence: 99%
See 1 more Smart Citation
“…For the first case, Herr et al [27] have discovered that the velocity profile is a function of the average z potential in a capillary. More recently, Salim et al [28] studied EOF in micro-channels influenced by lysozyme adsorption. The results showed that the EOF decreased with increasing lysozyme adsorption.…”
Section: Simulation Of Breakthrough Behaviormentioning
confidence: 98%
“…Recently, plasma patterning of microfluidic channels has received significant attention. [28][29][30][31]46,71,72 In most cases, microchannel patterning was achieved prebonding using appropriate masks or directed jets; however, only a few examples of postbonding treatment have been reported. [28][29][30][31]72,73 Postbonding plasma modification of polystyrene microchannels has been demonstrated by Evju et al 28 Platinum electrodes were engineered in the microchannel to generate an electric field along the length of the channel, Fig.…”
Section: Microplasmasmentioning
confidence: 99%